Effects of Acetic Anhydride toward Degree of Substitution on Acetylation Method of Sago Starch (Metroxylon sp) from Papua - Yuliya Andriani Nanggewa; Adi Setyo Purnomo; Surya Rosa Putra (Institut Teknologi Sepuluh Nopember, 2015)
Sago contains carbohydrates that are stored in the starch form. Starch is generally formed from two molecules of glucose polymer, namely amylose and amylopectin, which its composition varies for each type of starch [1]. The weakness of starch can be overcome through a modification of the functional properties of starch to expand sago starch. Chemical modification of starches can enlarge the range of certain starch physical properties of the parent starch [2] and enhance their use in a number of applications found in industrial processes and food manufacture. Chemical modification of starch can be performed by various methods such as acetylation. Generally, native starch has a low Degree of Substitution (DS) because of their limited degree or reaction on the granule surface. Increasing DS can be obtained by modification of native starch through acetylation reaction using few catalysts such as pyridine and NaOH. Several researchers have reported the effects of acetylation on many sort of starch sources such potato, corn, pea and cassava [3-5]. There are few studies about the effects of acetylation of starches with a wide range of amylose contents. We have carried out some work on effects of acetic anhydride concentration toward DS value of native and modified sago starch from Papua.